Synthesis of Naphthalimine‐derived Dye and Its Applications in Fluorescent Imaging and Dyeing Surgical Suture Materials. Issue 11 (26th March 2018) - Xiong, Xiaoqing; Zhi, Weiru; Yan, Jun; Song, Wenjing; Du, Hui; Zhao, Hongjuan; Li, Feixia; Song, Fengling; Sun, Yanfeng; Zheng, Laijiu
Abstract: In this study, NP‐indometacin, which was based on the two‐photon naphthalimine, was designed and synthesized. The anti‐inflammatory material indometacin was introduced intoNP‐indometacin so that the toxicity of this fluorescent dye was reduced when applied to living organisms.NP‐indometacin had high fluorescence quantum efficiency (0.98 in DMSO), a large Stokes shift (>77 nm) and feasible two‐photon action cross section (45 GM in DMSO).NP‐indometacin was utilized for the fluorescence imaging of living cells, and the high cell viability rate (>80%) indicated that this material had low toxicity in living organisms.NP‐indometacin was used to dye absorbable collagen surgical suture and constructed fluorescent surgical suture. It was found by one‐ and two‐photon fluorescence imaging thatNP‐indometacin distributed uniformly both outside and inside the sutures. Therefore, the straightforward synthesis ofNP‐indometacin and the wide availability of its constituents mean that it could both be highly useful for the observation of the healing of wounds and as a fluorescent warning material that is used in vivo . Abstract : NP‐indometacin was designed and synthesized. It had high fluorescence quantum efficiency and a large Stokes shift (>77 nm). It was utilized for the fluorescence imaging of living cells. The high cell viability rate (>80%) indicated that it had low toxicity in living organisms. Therefore, NP‐indometacin was applied in constructing fluorescent surgical sutures. One‐ and two‐photon fluorescence imaging indicated that NP‐indometacin distributed uniformly both outside and inside the sutures.